A new species of the genus Clastopus Fairmaire, 1898 (Coleoptera: Tenebrionidae: Pedinini) from Madagascar - Iwan, Dariusz; Kamiński, Marcin Jan; Aalbu, Rolf (Zootaxa, 2012)
A new species of the genus Clastopus Fairmaire, 1898 is described and illustrated. At present this genus consists of five speciesdistributed on the island of Madagascar: C. aberlenci Iwan, 2005, C. eurynotoides Fairmaire, 1898, C. ordinarius (Iwan, 1996),C. tenuiculus (Iwan, 1996) and C. griswoldi sp. nov. The material studied was acquired from California Academy of Sciences expeditions conducted between 2000 and 2002. A key is proposed to the species of Clastopus.